(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article explores effective strategies and technologies for teaching linguistic-cognitive analysis to future primary school teachers. It synthesizes current research on language support strategies, cognitive approaches to language learning, and linguistically responsive teaching. The paper highlights the importance of integrating advanced pedagogical methods with innovative technological tools to enhance the linguistic and cognitive development of young learners. It also discusses the necessity of continuous professional development for teachers in this critical area. The aim is to provide a comprehensive framework that can guide teacher education programs in preparing highly competent primary school educators capable of fostering robust language and cognitive skills in their students.